Etika sebagai Kriteria Perkembangan Moral Bisnis - Nagel, Julius F. (Kajian Manajemen dan Bisnis, 2010)
Ethics is a branch of philosophy relating to the "goodness (rightness)" or morality (ethics) of human behavior in this sense, ethics is defined as rules that cannot be breached from behavior accepted by society as good or bad. While the determination of good and bad is a problem, this is always changing. Business ethics are the standard values that guide or serve as a reference for managers and employees in decision-making in order to operate business ethically. Once, the paradigm of ethics and business were two different worlds until such time that ethics and business are intimately related as the synergy between ethics and profit. Precisely in this era of intense competition, good corporate reputation based on business ethics is a competitive advantage that will be difficult to imitate. Business ethics in business practices becomes very crucial and enjoins the company to meet it. Consistently applying business ethics, the organization creates good conditions toward a healthy organization. Finally, the application of business ethics in the form of good corporate governance can create a business climate that is efficient and transparent. Business can lake place smoothly when ethics is taken as a guide to business activities.